STRAIN LOCALIZATION PECULIARITIES AND DISTRIBUTION OF ACOUSTIC EMISSION SOURCES IN ROCK SAMPLES TESTED BY UNIAXIAL COMPRESSION AND EXPOSED TO ELECTRIC PULSES - V. A. Mubassarova; L. M. Bogomolov; A. S. Zakupin; I. A. Panteleev; O. B. Naimark (Геодинамика и тектонофизика, 2015)
Results of uniaxial compression tests of rock samples in electromagnetic fields are presented. The experiments were performed in the Laboratory of Basic Physics of Strength, Institute of Continuous Media Mechanics, Ural Branch of RAS (ICMM). Deformation of samples was studied, and acoustic emission (AE) signals were recorded. During the tests, loads varied by stages. Specimens of granite from the Kainda deposit in Kyrgyzstan (similar to samples tested at the Research Station of RAS, hereafter RS RAS) were subject to electric pulses at specified levels of compression load. The electric pulses supply was galvanic; two graphite electrodes were fixed at opposite sides of each specimen. The multichannel Amsy-5 Vallen System was used to record AE signals in the six-channel mode, which provided for determination of spatial locations of AE sources. Strain of the specimens was studied with application of original methods of strain computation based on analyses of optical images of deformed specimen surfaces in LaVISION Strain Master System.Acoustic emission experiment data were interpreted on the basis of analyses of the AE activity in time, i.e. the number of AE events per second, and analyses of signals’ energy and AE sources’ locations, i.e. defects.The experiment was conducted at ICMM with the use of the set of equipment with advanced diagnostic capabilities (as compared to earlier experiments described in [Zakupin et al., 2006a, 2006b; Bogomolov et al., 2004]). It can provide new information on properties of acoustic emission and deformation responses of loaded rock specimens to external electric pulses.The research task also included verification of reproducibility of the effect (AE activity) when fracturing rates responded to electrical pulses, which was revealed earlier in studies conducted at RS RAS. In terms of the principle of randomization, such verification is methodologically significant as new effects, i.e. physical laws, can be considered fully indubitable if they prove stable when some parameters of the experiment are changed. Parameters may be arbitrarily modified within a small range, and randomization is thus another common statistical significance criterion for sample sets obtained at the same conditions. At ICMM, the experiments were conducted in compliance with the principle of randomization [Bogomolov et al., 2011]. In this respect, the material of specimens, loading conditions and characteristics of the electrical pulses source were similar to those in the experiments at RS RAS.As evidenced by the experiments, during electromagnetic field stimulation, the AE activity is manyfold higher than the background activity before the impact. This supports the research results reviewed in [Bogomolov et al., 2011] concerning the AE activity increment of 20 % due to electric pulses in the field twice less strong than that in our experiments at ICMM.The AE energy distribution analysis shows that cumulative distributions of the number of AE signals vs energy (i.e. the number of AE signals which energy exceeds a specified threshold value) are power-behaved. This is equivalent to the linear plot of distribution in log units of energy and relative events number, similarly to the case of Gutenberg–Richter law for earthquakes. It is noted that for the logarithmic graphs of distribution by energy, angular coefficients (b-factors) are somewhat different in the period of electric impact and in no-impact periods, which shows that the ratio of AE signals with higher energy indicators is increased in case of external impacts. Such a difference is most evident at the near-critical load when compression amounts to 0.94 fracturing stress value.According to data from the AE source location system, it is revealed that impacts of the electric field are accompanied by redistribution of AE sources through the specimen volume when compression is below 0.9 maximum stress value, which corresponds to the stage of diffusive accumulation of defects. The location system can be effectively applied when events with high amplitudes are accumulated in sufficient number. In this regard, clustering of AE sources (defects) in the area of a future fault was recorded only during the measuring test when the AE activity was quite high at the constant load.As shown by data from the optical diagnostics set of equipment, LаVision Strain Master System, deformation of a specimen takes place in a non-uniform pattern over its surface, which is manifested as consecutively propagating waves of localized strain. This conclusion contributes to the research results obtained earlier for rock samples under tension and compression [Panteleev et al., 2013b, 2013c, 2013d]. Localized axial strain waves and localized radial strain waves (when material particles move in the direction perpendicular to the compression direction) are concurrently observed. Such localized strain waves are ‘slow’ – they propagate at velocities that are by six or seven orders lower than the intrinsic velocity of sound propagation in the material. This observation correlates with the research results obtained earlier in studies of strain localization forms in the course of rock deformation [Zuev, 2011; Zuev et al., 2012].When the loaded specimen is impacted by the electromagnetic field, maximum strain values are slightly decreased in comparison with those in the ordinary case (when only compressive load is applied). This trend seems to be a specific feature of changes in localization of deformation in the loaded rock samples impacted by electric pulses. Besides, the experiments demonstrate that a source of macro-destruction can be induced by the influence of an external electromagnetic field, and the growth of a nucleus of such source can be stabilized during the impact. The above conclusions correlate with the statistical model of a solid body with defects which is developed in ICMM [Panteleev et al., 2011, 2012, 2013a].